Prospect of Dairy Goat Production for Small-Scale Enterprise in Payakumbuh West Sumatra - Kurnia, Yulianti Fitri; Ferawati; Reswati; Khalil (Pakistan Journal of Nutrition, 2015)
Twenty-five goat farms were surveyed to gain data and information about population, farming practices, goat performances and market prospect. Data were then analyzed to compare the prospective of dairy goat farm in compare to meat-types as a livestock enterprise suitable for small-scale or part time farmers. Three dairy goat farms were then selected to define milk production, quality and marketing. Samples of fresh milk were taken from each farm and analyzed for microbial pathogens and physical characteristics. Results found from the 25-selected farms, there were 14 farms (56%) raising meat-type goat and 11 dairy goat farms (44%), but the total population of dairy goat of about 395 animals was much higher than that of meat type goat of 200 animals. Each dairy goat farm kept about 35.9 animals, while meat-type goats were only 14.3 animals. Dairy goat farm has better prospect in compare to meat-types as an alternative livestock enterprise suitable for small-scale farmer or part-time livestock producer in Payakumbuh region. The mean values of total plate counts and Coliforms were found in the range of 8.04-8.46 and 0.72-4.25 log CFU/ml, respectively, while Staphylococcus aureus and Escherichia coli were not detected. The physical characteristics of fresh goat milk from Payakumbuh met the national standard. The potential market for goat milk and higher price of bucks made the farmer to be able to increase their farm scale and to raise their goats more intensively in order to achieve optimum production performances and incomes.